2022
DOI: 10.3389/fmicb.2022.989183
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 2 signaling pathway activation contributes to a highly efficient inflammatory response in Japanese encephalitis virus-infected mouse microglial cells by proteomics

Abstract: Thousands of people die each year from Japanese encephalitis (JE) caused by the Japanese encephalitis virus (JEV), probably due to exacerbation of the inflammatory response that impairs the course of the disease. Microglia are mononuclear phagocytic cells located within the parenchyma of the central nervous system; these play a key role in the innate immune response against JEV infections. However, the involvement of toll-like receptor 2 (TLR2) in the inflammatory response during the early stages of JEV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Recent studies have highlighted the roles of TLRs in CNS viral infection. For example, in BV2 microglial cells infected with JEV, the activation of TLR2 and TLR6 is key to the production of inflammatory factors, such as TNF-α, CCL3, IL-1β, and iNOS, via the PI3K-AKT pathway [ 128 ]. Moreover, JEV induces let7a/b expression in N9 microglia, and let7a/b can activate the NOTCH-TLR7 pathway and induce NF-κB activation and cytokine production [ 129 ].…”
Section: Involvement Of Tlrs In Neuroinflammation and Neurodegenerationmentioning
confidence: 99%
“…Recent studies have highlighted the roles of TLRs in CNS viral infection. For example, in BV2 microglial cells infected with JEV, the activation of TLR2 and TLR6 is key to the production of inflammatory factors, such as TNF-α, CCL3, IL-1β, and iNOS, via the PI3K-AKT pathway [ 128 ]. Moreover, JEV induces let7a/b expression in N9 microglia, and let7a/b can activate the NOTCH-TLR7 pathway and induce NF-κB activation and cytokine production [ 129 ].…”
Section: Involvement Of Tlrs In Neuroinflammation and Neurodegenerationmentioning
confidence: 99%
“…To date, limited information is available regarding the risk factors associated with poor prognosis in severe adult JE cases. The Japanese Encephalitis Virus can directly induce neuronal damage, and the resulting inflammation can exacerbate this effect ( 5 ). Previous studies have indicated a correlation between the innate immune response and fatal outcomes in flavivirus infections ( 6 ).…”
Section: Introductionmentioning
confidence: 99%